Anatomical Variations of the Distal Humeral Septum: A Cross-Sectional Study on the Presence of the Supratrochlear Foramen (Community Based Medical Journal, 2026)
A cross-sectional, descriptive study was conducted in the Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh, between July 2021 and June 2022, to assess the prevalence and morphological dimensions of the supratrochlear foramen of the humerus in a Bangladeshi population. A total of 100 dried humeri (43 right-sided and 57 left-sided) of unknown sex and age were included, selected through purposive sampling. Damaged, unossified, or fractured humeri were excluded to ensure the accuracy of this study. In this study, among 43 right humeri, the supratrochlear foramen was observed in 10(23.25%) cases, while it was absent in 33(76.75%) cases. Among 57 left humeri, 17(29.82%) had the supratrochlear foramen, and it was absent in 40(70.18%) cases. The anatomical knowledge of the supratrochlear foramen is essential for professionals such as anthropologists, orthopedic surgeons, and radiologists. Understanding its presence and variations is particularly important in the context of supracondylar fractures of the humerus, as it can aid in accurate diagnosis, treatment planning, and the avoidance of potential complications during surgical procedures or imaging.CBMJ 2026 July: Vol. 15 No. 02 P:145-149